2010
DOI: 10.1080/14742831003603349
|View full text |Cite
|
Sign up to set email alerts
|

Local to Global Activism: The Movement to Protect the Rights of Refugees and Asylum Seekers

Abstract: This paper explores the emergence of social movement action on the rights of asylum seekers in the Australian case. It focuses on new and growing collective action in the context of the neoliberal and neoconservative government of John Howard (1996 -2007) and situates this rise within a generalizable and universal human rights movement. The detention and deportation of asylum seekers, which resulted in revitalized collective action, is detailed as the trigger for collective action. The paper argues that a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Citizens, grassroots associations, advocacy groups and social movements organize and participate in collective actions, activate their networks, and share their knowledge and influence with marginalized beneficiaries. As numerous studies have demonstrated, solidarity protests have become a collective actor in challenging the machinery of asylum and deportation (Freedman 2009;Tazreiter 2010;Hasselberg 2014).…”
Section: Solidarity Protest Against Deportationsmentioning
confidence: 99%
“…Citizens, grassroots associations, advocacy groups and social movements organize and participate in collective actions, activate their networks, and share their knowledge and influence with marginalized beneficiaries. As numerous studies have demonstrated, solidarity protests have become a collective actor in challenging the machinery of asylum and deportation (Freedman 2009;Tazreiter 2010;Hasselberg 2014).…”
Section: Solidarity Protest Against Deportationsmentioning
confidence: 99%
“…Often alternative ideas about belonging and citizenship are being articulated at the local, city level, for example around the sans-papiers movement in France (ISIN, 2005;MCNEVIN, 2011;NICHOLLS, 2011). In the academic literature, there has recently been more attention on local social and political protests around asylum policies and deportations (ALINK, 2006;GIBNEY, 2008;TAZREITER, 2010;VERSTEEGT and MAUSSEN, 2012). In this article, we want to contribute to this emerging literature by looking at the political dimension of interactions between national and municipal policy actors (governments and politicians as well as officials, bureaucrats and professionals).…”
Section: Legitimacy Of Immigration Control Policies: a Framework For mentioning
confidence: 99%
“…Citizens, grassroots associations, advocacy groups and social movements organize and participate in collective actions, activate their networks, and share their knowledge and influence with marginalized beneficiaries. As numerous studies have demonstrated, solidarity protests have become a collective actor in challenging the machinery of asylum and deportation (Freedman 2009;Tazreiter 2010; Hasselberg 2014).Drawing on existing literature and research findings from the Taking Sides project 1 , we can identify three main features in solidarity movements. Firstly, the individuals and informal networks which dominate protest groups act in the interests of others.…”
mentioning
confidence: 99%
“…To which extent do claims raised in the protest events focus on the implementation of certain deportations and individual solutions, and to which extent do they focus on policy reforms (Jasper 2014)? Are protest activities organized at a local or national level, or do they even qualify as a transnational movement that tackles not only individual deportations but restrictive migration and border regimes Tazreiter 2010)? This chapter addresses these questions by presenting a comparison of antideportation protest activities across three countries and over 20 years . A protest event analysis (PEA, i.a.…”
mentioning
confidence: 99%
See 1 more Smart Citation